Exploitation of Social Media in Education: Building or Destroying Equality - Sahrona; Maesaroh Lubis; Dodo Martado (Jurnal Ilmiah Sekolah Dasar, 2024)
Social media has become an integral part of modern life and has a complex impact on various aspects of life, including education, health, psychology, and the economy. However, vulnerable groups that experience digital access and literacy gaps are often disproportionately affected. This research aims to explore in depth the impact of social media on vulnerable groups in the context of digital inequality. This type of research is qualitative descriptive with a literature study approach. The subjects in this study are in the form of relevant secondary data sources, such as scientific journals, institutional reports, and reliable articles. The data collection technique is carried out through literature review, while the data analysis uses thematic analysis to identify the main patterns and themes of social media impact. The results show that social media has positive potential in increasing educational participation and access to information, but it also poses risks such as exposure to negative content, mental health disorders, and strengthening the digital divide, especially in individuals from low economic groups and with limited digital literacy. The conclusion of this study emphasizes the importance of systematic interventions in the form of strengthening digital literacy, equitable access to technology, and inclusive content regulation. The implications of the results of this study encourage the need for strategic policies to ensure safe, equitable, and empowering use of social media in supporting education and the welfare of the community at large.